2020
DOI: 10.1016/j.lungcan.2020.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling by targeted RNA sequencing in pathological stage I lung adenocarcinoma with a solid component

Abstract: Solid predominant adenocarcinoma is considered an independent predictor of an unfavorable prognosis in patients with stage I lung adenocarcinoma (LUAD). Furthermore, solid minor components are related to poor prognosis in patients with stage I LUAD. Therefore, it is imperative to elucidate the molecular determinants of the malignant potential of solid components (SC). Several studies reported the gene expression profiling specific for lepidic predominant adenocarcinoma or solid predominant adenocarcinoma, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…TAF7 may play an important role in cancer, as evidenced by a study of breast cancer that found significantly increased expression levels of TAF7 in tumor tissue, which was correlated with the invasive and metastatic potential of breast cancer [ 72 ]. Additionally, other studies have found abnormal expression of TAF7 in various types of cancer, including gliomas and lung adenocarcinomas [ 73 75 ]. These findings suggest that TAF7 may be involved in the development and progression of esophageal tumors and may be a potential therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…TAF7 may play an important role in cancer, as evidenced by a study of breast cancer that found significantly increased expression levels of TAF7 in tumor tissue, which was correlated with the invasive and metastatic potential of breast cancer [ 72 ]. Additionally, other studies have found abnormal expression of TAF7 in various types of cancer, including gliomas and lung adenocarcinomas [ 73 75 ]. These findings suggest that TAF7 may be involved in the development and progression of esophageal tumors and may be a potential therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse embryonic fibroblasts with TAF7 deletion halt transcription globally and stop proliferation, hinting at the importance of TAF7 for the survival and proliferation of embryonic cells 36 . In addition, some studies noted that TAF7 was frequently overexpressed in various cancers through bioinformatics analysis and experimental verification including breast cancer 24 , glioblastoma 25 , lung adenocarcinoma 37 and colorectal cancer 38 . Consistent with previous reports, our results indicated that TAF7 silencing inhibited ccRCC progression through reducing cell activity, increasing apoptosis, arresting S into G2/M cell cycle and diminishing migration, which substantiated the oncogenic capacity of TAF7 in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…As a new regulator of PD-L1, CMTM6 co-localizes with the PD-L1 protein and stabilizes PD-L1 expression on the cell surface (Burr et al, 2017 ; Mezzadra et al, 2017 ). The anti-tumor response and immunological escape are caused by the stabilizing action of CMTM6 on PD-L1, which promotes PD-L1 on the tumor cell membrane and attaches to PD-1 on activated T cells (Kidokoro et al, 2020 ; Xie et al, 2019 ). Therefore, an increasing amount of research is focused on the interaction and association involving CMTM6 and PD-L1 in many cancers and even some inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%